Evaluating the patterns of spatiotemporal trends of root zone soil moisture in major climate regions in East Asia. Issue 15 (2nd August 2017) - Zohaib, Muhammad; Kim, Hyunglok; Choi, Minha
Abstract: Root zone soil moisture (RZSM) is a crucial variable in land‐atmosphere interactions. Evaluating the spatiotemporal trends and variability patterns of RZSM are essential for discerning the anthropogenic and climate change effects on the regional and global hydrological cycles. In this study, the trends of RZSM, computed by the exponential filter from the European Space Agency's Climate Change Initiative soil moisture, were evaluated in major climate regions of East Asia from 1982 to 2014. Moreover, the trends of RZSM were compared to the trends of precipitation ( P ), skin temperature ( T skin ), and actual evapotranspiration (AET) to investigate how they influence the RZSM trends in each climate region. Drying trends were predominant in arid and continental regions, whereas wetting trends were found in the tropical and temperate regions. The increasing trends of T skin and AET cause drying in arid and continental regions, whereas in tropical regions, these cause wetting trends, which might be due to convective P . In temperate regions, despite decreasing P and increasing T skin, the RZSM trend was increasing, attributed to the intensive irrigation activities in these regions. This is probably the first time to analyze the long‐term trends of RZSM in different climate regions. Hence, the results of this study will improve our understanding of the regional and global hydrological cycles. Despite certain limitations, the results of this study may be useful for improving and developing climate models and predicting long‐term vast scale natural disasters such as drought, dust outbreaks, floods, and heat waves. Key Points: The influencing mechanism of precipitation and skin temperature on root zone soil moisture trend is different in different climate regions Increasing precipitation, temperature, and evapotranspiration causes wetting trends in tropical regions while drying trends in arid regions Irrigation causes a wetting trend of root zone soil moisture despite decreasing precipitation and rising temperature in temperate regions